An Experimental Study to Reduce the Fracture Pressure of High Strength Rocks Using a Novel Thermochemical Fracturing Approach. (19th August 2019) - Tariq, Zeeshan; Mahmoud, Mohamed A.; Abdulraheem, A.; Al-Nakhli, Ayman; BaTaweel, Mohammed
Abstract : Current oil prices and global financial situations underline the need for the best engineering practices to recover remaining oil from unconventional hydrocarbon reservoirs. These hydrocarbon reservoirs are mostly situated in deep and overpressured formations, with high rock strength and integrity. Breakdown pressure of the rock is a function of their tensile strength and in situ stresses acting on them. Fracturing stimulation techniques become challenging when treating these types of rocks, and many cases approached to the operational limits. This leaves a small operational window to initiate and place hydraulic fractures. In this study, a new methodology to reduce the breakdown pressure of the high stressed rock is presented. The new method enables the fracturing of high stressed rocks more economically and efficiently. Fracturing experiments were carried out on different blocks, and the breakdown pressure was measured by creating a simulated borehole at the center of the block. Thermochemical fluids were injected to create the microfractures. These microfractures improved the permeability and porosity and reduced the elastic strength of the subjected samples prior to the main hydraulic fracturing job. The posttreatment experimental analysis confirmed the presence of microfractures which were originated due to the pressure pulse generated from the thermochemical reaction. The results of this study showed that the newly formulated method of thermochemical fracturing reduced the breakdown pressure by 38% in slim borehole blocks and 60% in large borehole blocks. Results also showed that the breakdown time to initiate the fractures was reduced to 19% in slim borehole blocks and 17% in large borehole blocks. The reduction in breakdown pressure and breakdown time happened due to the creation of microfractures by the pressure rise phenomenon in a new thermochemical fracturing approach.